A tale of four cities: the boundaries of blackness for Ethiopian immigrants in Washington, DC, Tel Aviv, Rome, and Melbourne. (2nd January 2019) - Trujillo-Pagán, Nicole
ABSTRACT: Scholars increasingly view urban areas as fragmented spaces where migrants are policed in ways that promote differential access to mobility, but the glocal meanings of race are often undertheorized. This paper explores the mobility experiences of Ethiopian migrants in four cities: Washington, DC, Tel Aviv, Rome, and Melbourne. Using a textual analysis of newspaper coverage in each city, the analysis finds that media and police often act as agents who racialize Ethiopian migrants relative to native minorities and other migrants. The paper concludes that the experiences Ethiopian immigrants faced in urban areas were informed by glocal meanings of race (blackness); they were shaped in relation to not only other migrants and native minorities, but also a globalized discourse on immigration.